Problematika Pembatalan Putusan Arbitrase BPSK oleh Pengadilan Negeri Batam Ditinjau dari Asas Kepastian Hukum - Christy, Christy (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
The UUPK aims to create a fast, simple, and cheap consumer dispute resolution process. However, the BPSK arbitration decision is deemed not to provide a guarantee of legal certainty, so it can be annulled by the Batam District Court. This research found that this experience would greatly help businesses if they did not violate UUPK. BPSK believes that the problems submitted to it should not be rejected by BPSK and will be handled according to procedures. Even though it is not stated in the agreement, BPSK will also continue to examine the complaint, or it will be recommended that the complaint be continued to court or other authorized institutions, such as the OJK LAPS. By number 11 article 1 UUPK, Minister of Industry and Trade Decree no. 350/MPP/Kep/12/2001 and Minister of Trade Regulation no. 06/M-DAG/PER/2/2017, BPSK has the legal authority to handle all matters relating to consumer disputes. BPSK can only limit arbitration settlements by proving that consumers have suffered losses according to Article 52 UUPK. So, to increase legal certainty regarding arbitration decisions made by BPSK, it is necessary to improve the monitoring process of BPSK's performance so that BPSK can provide better services. Furthermore, it is very important to provide clearer and more detailed guidelines regarding decision-making criteria for BPSK in handling consumer disputes.